Ensuring Housing Rights: Legal Analysis of Rusunawa Implementation in Purbalingga Regency - Rohmatino, Hasan Akmal (Indonesian Journal of Agrarian Law, 2024)
This study discusses the legal framework and the implementation of the management and occupancy system of Simple Rental Flats (Rusunawa) in Purbalingga Regency, which are intended for low-income communities (MBR). The purpose of this research is to analyze the compliance of Rusunawa implementation in Purbalingga with applicable national and regional legal regulations. The research method used is normative juridical, employing a statutory approach and secondary data consisting of laws, government regulations, official documents, and information from related agencies. The findings indicate that the development and management of Rusunawa in Purbalingga are in accordance with Law Number 20 of 2011, Government Regulation Number 12 of 2021, Ministry of Public Works Regulation No. 14/PRT/M/2017, and Purbalingga Regional Regulations. However, ongoing supervision and improvements in technical regulations are necessary to ensure that the social benefits of Rusunawa are maximized and sustainable.